Rapid paralysis and hidden malignancy: acute motor axonal neuropathy revealing pleomorphic liposarcoma - Sathish Kumar Krishnan; Vijaya Sivalingam Ramalingam; Melissa Johnson (European Journal of Case Reports in Internal Medicine)
Guillain-Barré syndrome is an immune-mediated neuropathy characterised by acute-onset of symmetric, ascending motor weakness and areflexia. Acute motor axonal neuropathy, a severe axonal variant, is distinguished by direct axonal injury and poor functional recovery. Although infections are recognised triggers for Guillain-Barré syndrome, it is notable that up to half of cases occur without a preceding infectious event, suggesting that other factors such as underlying malignancy may contribute to disease onset. We present a rare and fatal case of acute motor axonal neuropathy in a 70-year-old woman, who was ultimately found to have an underlying pleomorphic liposarcoma. The patient presented with one week of progressive weakness, fatigue and encephalopathy. She required urgent mechanical ventilation due to respiratory failure; imaging identified multiple bilateral pulmonary nodules. Neurologic evaluation confirmed acute motor axonal neuropathy through nerve conduction studies and cerebrospinal fluid analysis, which showed albuminocytologic dissociation and positive anti-GM1 IgG antibodies. Despite standard treatment with intravenous immunoglobulin, the patient experienced no neurological recovery. Further imaging revealed a large pelvic mass, that was not present on a scan performed two months earlier. A biopsy confirmed pleomorphic liposarcoma, a rare and aggressive soft tissue sarcoma. Paraneoplastic panel testing was negative for onconeural antibodies, yet the clinical context raised suspicion for an immune-mediated, tumour-associated neuropathy. Clinicians should maintain a high level of suspicion of underlying malignancy in patients with Guillain-Barré syndrome, especially in the absence of preceding infection and with rapid neurological decline.